[beta]-Aminobutyric Acid Induces the Accumulation of Pathogenesis-Related Proteins in Tomato (Lycopersicon esculentum L.) Plants and Resistance to Late Blight Infection Caused by Phytophthora infestans. - Cohen, Y. (1994)
Tomato (Lycopersicon esculentum L.) plants were sprayed with aqueous solutions of isomers of aminobutyric acid and were either analyzed for the accumulation of pathogenesis-related (PR) proteins or challenged with the late blight fungal agent Phytophthora infestans. The [beta] isomer of aminobutyric acid induced the accumulation of high levels of three proteins: P14a, [beta]-1,3 glucanase, and chitinase. These proteins either did not accumulate or accumulated to a much lower level in [alpha]- or [gamma]-aminobutyric acid-treated plants. Plants pretreated with [alpha]-, [beta]-, and [gamma]-aminobutyric acid were protected up to 11 d to an extent of 35, 92, and 6%, respectively, against a challenge infection with P. infestans. Protection by [beta]-aminobutyric acid was afforded against the blight even when the chemical was applied 1 d postinoculation. Examination of ethylene evolution showed that [alpha]-aminobutyric acid induced the production of 3-fold higher levels of ethylene compared with [beta]-aminobutyric acid, whereas [gamma]-aminobutyric acid induced no ethylene production. In addition, silver thiosulfate, a potent inhibitor of ethylene action, did not abolish the resistance induced by [beta]-aminobutyric acid. The results are consistent with the possibility that [beta]-aminobutyric acid protects tomato foliage against the late blight disease by a mechanism that is not mediated by ethylene and that PR proteins can be involved in induced resistance.